Implementation of the Progressive Healthy Nutrition Action Program Among the Muhammadiyah Generation (GenMu) at Muhammadiyah Junior High School 1 in Ternate - Suryani Mansyur; Diah Merdekawati Surasno; Agustin Rahayu; Andiani Andiani; Tati Sumiati; Nani Supriyatni; Yusnita Yusnita; Monisa A Hi Djafar; Ramli Ramli; Suryadi M. Ali; Mayasari Soamole (BIOSAINSTEK, 2026)
Data from Basic Health Research 2018 shows that approximately 32% of teenager girls in Indonesia experience anemia, primarily caused by iron deficiency. Furthermore, the 2022 Indonesian Nutritional Status Survey (SSGI) reported that breakfast habits among school aged children remain low and adequate physical activity has not yet become a routine practice in school environments. These conditions has an impact on decreased concentration in learning, academic achievement, and physical fitness, and in the long term can increase the risk of stunting in the next generation. Therefore, early intervention is urgently required. In response to this issue, the Indonesian government, through the Ministry of Health, initiated the Progressive Healthy Nutrition Action Program. This program integrates balanced nutrition education, the promotion of healthy breakfast habits, consumption of iron supplementation, and regular physical activity in schools. The purpose of community service is to improve female students’ knowledge of balanced nutrition and healthy lifestyles. The implementation activities included group exercise sessions, healthy breakfast activities, balanced nutrition counseling, and measurement of mid-upper arm circumference (MUAC). The method used was pre-posttest evaluation and analyzed using paired t-test analysis. The results demonstrated a positive impact on participants’ knowledge levels. The average knowledge score increased from 4.23 to 7.03 after the intervention, with a mean difference of 2.797. In addition, the average MUAC of participants was 22.194 cm, indicating chronic energy deficiency status. These findings suggest that the educational intervention effectively improved students’ understanding of balanced nutrition and can be considered effective as a form of educational intervention in the school environment.